The Islamic Educational Values in The Batimung Tradition : Implications for The Young Generation in Banjar District - Nimah Nimah; Ach Fatori; Panggih Prabowo R.S. (Journal of Southern Sociological Studies, 2025)
This study investigates the Islamic educational values embodied in the Batimung tradition, a ritual steam bath practiced by the Banjar ethnic group in South Kalimantan, Indonesia. Positioned within a Global South framework, Batimung is analyzed as a site of cultural resilience and pedagogical innovation amid the pressures of globalization and epistemic hegemony. Utilizing a qualitative literature review, the study draws from academic sources published between 2015 and 2024 to examine Batimung’s moral, spiritual, ecological, and gendered dimensions. Findings reveal that Batimung fosters key Islamic values such as thaharah (purity), tazkiyah al-nafs (self-purification), muamalah (social ethics), and communal harmony through embodied, affective learning. Women’s central roles in ritual performance further highlight its function as a matrifocal space for moral transmission. Beyond its symbolic significance, Batimung offers transformative potential for Islamic education through culturally grounded curricula, experiential pedagogy, and environmental ethics. The study advocates for the formal recognition of Batimung within Islamic education policy and practice, emphasizing its relevance for character formation, intergenerational knowledge transfer, and epistemological decolonization. Ultimately, Batimung represents a living educational system that integrates body, spirit, nature, and community—offering a holistic and context-responsive model for Islamic character education in the 21st century.